2021
DOI: 10.1016/j.psj.2021.101398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amino acid levels during rearing on Cobb 500 slow-feathering broiler breeders: 2. Reproductive performance

Abstract: Crude protein and amino acid ( AA ) content in rearing diets affect body composition and reproductive performance. This study evaluated the effects of 4 dietary AA levels during rearing on BW, egg production and composition, fertility, hatchability, and embryo mortality up to 65 wk of age on Cobb 500 slow-feathering ( SF ) broiler breeders. The treatments consisted in 80% (low-AA), 90% (moderate-AA), 100% (standard-AA), and 110% (high-AA) of the AA recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…Overall, high and persistent laying rate led to high cumulative egg production in strain A and strain B by the end of the study (above 165 eggs/hen on average). Compared to previous research, the strains in our study had higher cumulative egg production than conventional broiler breeders (e.g., Ross 308: 143 eggs/hen [ Arrazola et al., 2019b ; Aviagen, 2021a], Ross 708: 137 eggs/hen [ van der Klein et al., 2018 , Aviagen, 2021b], and Cobb 500: 138 eggs/hen [ Arabinar et al., 2020 ; Oviedo-Rodon et al., 2021 ]). Previous research with alternative strains also concluded that slower growing strains of broiler breeders can achieve higher egg production than conventional feed-restricted broiler breeders ( Heck et al., 2004 ; Gebhardt-Henrich et al., 2018 ).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Overall, high and persistent laying rate led to high cumulative egg production in strain A and strain B by the end of the study (above 165 eggs/hen on average). Compared to previous research, the strains in our study had higher cumulative egg production than conventional broiler breeders (e.g., Ross 308: 143 eggs/hen [ Arrazola et al., 2019b ; Aviagen, 2021a], Ross 708: 137 eggs/hen [ van der Klein et al., 2018 , Aviagen, 2021b], and Cobb 500: 138 eggs/hen [ Arabinar et al., 2020 ; Oviedo-Rodon et al., 2021 ]). Previous research with alternative strains also concluded that slower growing strains of broiler breeders can achieve higher egg production than conventional feed-restricted broiler breeders ( Heck et al., 2004 ; Gebhardt-Henrich et al., 2018 ).…”
Section: Discussioncontrasting
confidence: 53%
“…Hens started laying earlier than expected according to breeding guidelines, and laying rate peaked at different ages among the hen strains. After the peak, laying rate persisted at a high rate for two of the hen strains (A and B) whereas laying rate dropped below 50% in 2 pens of strain C. In conventional broiler breeder hens, laying rate drops linearly after peak as body weight increases (e.g., Ross 308 [ van Emous et al., 2015a ; Arrazola et al., 2019b ], Ross 708 [van der Klein et al., 2018] , and Cobb 500 [ Arabinar et al., 2020 ; Oviedo-Rodon et al., 2021 ]). Certainly, fast growth rate and excessive fat accumulation negatively impact the reproductive performance and health of broiler breeders, and the severity of obesity-related problems depends on individual and strain susceptibility to lipotoxicity ( Heck et al., 2004 ; Chen et al, 2006 ; Renema et al., 2007 ; Walzem and Chen, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hens having larger breast meat may have more difficulties in exposing their cloaca for mating, which can lead to incomplete mating and decreased fertility ( Aviagen, 2018 ). In addition, hens provided with 110% lysine diets produced fewer eggs compared to when feeding according to recommendations during rear ( Oviedo-Rondon et al, 2021 ). Interestingly, feeding an 80% lysine diet also caused a slight reduction in egg production indicating the importance of feeding diets with balanced amino acids.…”
Section: Utilizing Amino Acid Balance and Functional Properties To Im...mentioning
confidence: 99%
“…The quality and amino acid balance in protein diets is essential for growth and reproduction performance (Oviedo-Rondón et al, 2021).…”
Section: Proteinmentioning
confidence: 99%